Dynamic projections of extreme sea levels for western Europe based on ocean and wind-wave modelling - A. A. Chaigneau; A. A. Chaigneau; A. A. Chaigneau; A. Melet; A. Voldoire; M. Irazoqui Apecechea; G. Reffray; S. Law-Chune; L. Aouf (Natural Hazards and Earth System Sciences)
Extreme sea levels (ESLs) are a major threat for low-lying coastal zones. Climate-change-induced sea level rise (SLR) will increase the frequency of ESLs. In this study, ocean and wind-wave regional simulations are used to produce dynamic projections of ESLs along the western European coastlines. Through a consistent modelling approach, the different contributions to ESLs, such as tides, storm surges, waves, and regionalized mean SLR, as well as most of their non-linear interactions, are included. This study aims at assessing the impact of dynamically simulating future changes in ESL drivers compared to a static approach that does not consider the impact of climate change on ESL distribution. Projected changes in ESLs are analysed using non-stationary extreme value analyses over the whole 1970–2100 period under the SSP5-8.5 and SSP1-2.6 scenarios. The impact of simulating dynamic changes in extremes is found to be statistically significant in the Mediterranean Sea, with differences in the decennial return level of up to +20 % compared to the static approach. This is attributed to the refined mean SLR simulated by the regional ocean general circulation model. In other parts of our region, we observed compensating projected changes between coastal ESL drivers, along with differences in timing among these drivers. This results in future changes in ESLs being primarily driven by mean SLR from the global climate model used as boundary conditions, with coastal contributions having a second-order effect, in line with previous research.